Pemikiran Kritis Lucy Irigaray dalam Linguistik - Pudjiati, Danti (Buletin Al-Turas, 2007)
This article is aimed to introduce a contemporary philosopher women from France named Luce Irigaray.She becomes well known as critisizing all of the written in public are rare to discuss about women significanlly.One of her studies Is in linguistics  entilled Je, tu, nous, Pour une Culturede la difference arguing about sex and gender in language. She examined  the women do not be the subjectin the language Instead of men. Furthermore,  feminine  pronoun is replaced for unimportant things whereas masculine pronounIs for Important  thing  based on French  culture.  She thinks language  has a essensial role as a means of communicationIn society and determined the position of women.